2011
DOI: 10.1590/s1517-83822011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cry2-type genes of Bacillus thuringiensis strains from soil-isolated of Sichuan basin, China

Abstract: Sichuan basin, situated in the west of China, is the fourth biggest basin in China. In order to describe a systematic study of the cry2-type genes resources from Bacillus thuringiensis strains of Sichuan basin, a total of 791 Bacillus thuringiensis strains have been screened from 2650 soil samples in different ecological regions. The method of PCR-restriction fragment length polymorphism (PCR-RFLP) was used to identify the type of cry2 genes. The results showed that 322 Bacillus thuringiensis strains harbored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Similar to our result, Sauka et al (2005) showed that among the native B. thuringiensis strains, 94.9% of them had cry2Aa/cry2Ab gene combination whereas 3.4% and 1.7% of them contained cry2Ab or cry2Aa, respectively. In addition, Liang et al (2011) reported that cry2Aa/cry2Ab gene combination was the most frequent (90.4%), whereas percentages of cry2Aa and cry2Ab positive genes in their B. thuringiensis strains were 6.8 and 2.5, respectively. In other words, occurrence of cry2Aa/cry2Ab gene combination was the most frequent compared to that of individual cry2-type genes in B. thuringiensis strains.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our result, Sauka et al (2005) showed that among the native B. thuringiensis strains, 94.9% of them had cry2Aa/cry2Ab gene combination whereas 3.4% and 1.7% of them contained cry2Ab or cry2Aa, respectively. In addition, Liang et al (2011) reported that cry2Aa/cry2Ab gene combination was the most frequent (90.4%), whereas percentages of cry2Aa and cry2Ab positive genes in their B. thuringiensis strains were 6.8 and 2.5, respectively. In other words, occurrence of cry2Aa/cry2Ab gene combination was the most frequent compared to that of individual cry2-type genes in B. thuringiensis strains.…”
Section: Discussionmentioning
confidence: 99%
“…Cry2Ab protein (ABC95996.1) showed maximum identity with pesticidal crystal protein Cry2Ab [ B.thuringiensis serovar kurstaki str ]. There has been an earlier report of Blastp analysis of Cry2 genes of B.thuringiensis isolated from soil [9]. …”
Section: Resultsmentioning
confidence: 99%
“…Until then, works with Cry2 protein against coleopterans had still not been reported. Although Cry1 proteins have originally been related in regards to their toxicity for lepidopterans, many studies have already reported their toxicity for coleopterans (10, 23, 25, 26, 30). These results evidence the toxic potential of Cry1 and Cry2 proteins against coleopterans, which until then was essentially associated to Cry3 and Cry9 proteins (11, 19).…”
Section: Resultsmentioning
confidence: 99%
“…Cry1 genes are most frequent in nature, representing over 43% of the reported cry genes. This class synthesizes proteins toxic mainly to the Lepidoptera order, while cry2 genes are toxic both to the Lepidoptera and Diptera orders (8, 23). Cross-order activity has been shown in 15 of the 87 pesticide crystal protein families, and most toxins were assessed for 10 species or less.…”
Section: Introductionmentioning
confidence: 99%